Strengthening English Language Ability at Universitas Islam Sumatera Utara with a Keyword-Based Model - Manugeren, M.; Wulan, Sri; Pardi; Mahid, Perveen Sonia (International Journal of English and Applied Linguistics (IJEAL), 2022)
This study aims to find an English learning model for adult students at Universitas Islam Sumatera Utara. The goal is to improve students' English skills at the institution. A simple model has the potential to improve students' English skills, especially adult students. This study uses a qualitative approach by percentage calculations. By using a purposive sampling method, the respondents of this study were academicians. The research data came from Likert-scale questionnaire scores given to the research sample. This study found that a keyword-based model is very good for teaching English to adult learners in a relatively short time and to help them understand the language well.